Constructing the Self in the Midst of Responsibility and Challenges: Narratives of Filipino Generation Z Breadwinners - Abaquita, Kathlynn Keith J.; Lemana, Henry II; Wei Lun, Wong; Accad, Mildred F.; Cahilog, Don T.; Sarmiento, Roxan T. (Journal of Education Culture and Society, 2026)
Aim. This study explores the lived narratives of Generation Z Filipinos who serve as primary breadwinners, with a focus on how they construct and negotiate their identity, relationships, and aspirations amid socio-emotional challenges.Methods. Using a narrative inquiry approach, three participants were purposively selected and interviewed to capture their complex experiences.Results. Through cross-theme analysis, three central themes emerged: premature adulthood and unchosen responsibility, emotional labour and the invisibility of struggle, and hope-driven resilience and moral consciousness. These themes reflect a reality where participants were thrust into adult roles due to familial crises such as poverty, illness, or abandonment. Despite emotional strain and invisible burdens, they sustained themselves through hope and a strong sense of moral duty.Conclusions. This study concludes that adversity among Generation Z Filipino breadwinners initiates dynamic processes of reintegration, often leading to the emergence of ethical agency and strengthened identity. The findings highlight the imperative for educational institutions and social systems to acknowledge the diverse and non-linear developmental trajectories of youth who assume adult responsibilities prematurely. Moreover, the study advocates for more inclusive and responsive psychosocial support structures, as well as expanded conceptualisations of youth development that account for the complexities of their lived realities.